Peduli Cegah Stunting Pada Anak di Kota Palangka Raya - Marhaeni Fajar Kurniati; Husen Arif Hidayat; Dessy Angreni; Deby Nuriadini; Ahsanu Amalaa (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Recently, stunting has been hotly discussed by many people, especially mothers. According to WHO, stunting is a child's growth and development disorder caused by a lack of nutritional intake, infection, or inadequate stimulation. The number of stunting sufferers in Indonesia according to the 2018 Riskesdas results continues to decline. Community service activities for UNISKA MAB Banjarmasin students with the theme "Care to Prevent Stunting in Children in the City of Palangka Raya" were carriedout on Monday 13 November 2023 and were attended by thousands of listeners streaming via the RRI Digital Pro2 Palangka Raya program. With registration via Google form 44 people, but when the streaming starts2,314 listeners were present in the RRI Digital comments column when the event took place. The activity was carried out through several stages, namely: distributing activity pamphlets/flayers on social media and going through the Google form registration stage and when the event took place with the opening stage from the Head of the UNIKSA MAB Banjarmasin Communication Science Masters Study Program , and continued with material presentations by 4 UNISKA MAB Banjarmasin